Justice for older people - Lesser, Harry. (Value Inquiry Book Series, 2012)
The authors of these papers vary in age, nationality and professional background. They share a belief that all too often older people are not treated justly or fairly, and also a belief that this is particularly true with regard to a proper respect for their dignity as people and a proper allocation of medical and social resources. Their papers, in various ways, give evidence as to what is happening and arguments, based on philosophical ethics, as to why it is wrong. The authors also have a range of proposals, backed by argument and evidence, and drawing on factual material as well as philosophical argument, as to what could be done to improve the situation. This is a book for anyone, whether themselves elderly, looking after an older person, professionally involved in working with older people, or simply realising that one day they will be old, who wants to learn about what is wrong with the present situation and how it might be made better.